Ø§ÙÙ ÙÙØ¬ Ø§ÙÙØÙÙ Ø¹ÙØ¯ Ø§ÙØ¨ØµØ±ÙÙÙ - Yasmadi, Yasmadi (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
the aim of the study is to identify the Arabic grammar based on Â Nahu. Formerly, Basrah scholars focused on their study to determine Nahu and Arabic grammar. Although they agreed with Kufah group that hadits and word sayings of Arabic people can become references to in determining syntactical structure (grammar) of Arabic language. Thus, theyÂ provide strong requirement to those references. Meanwhile the scholars made qiyas Â as ijma` as Nahu regulations.Â Â Copyright Â© 2015 by Al-Talim All right reserved